Study protocol for the ACTIVE SCHOOL study investigating two different strategies of physical activity to improve academic performance in Schoolchildren - Lise Sohl Jeppesen; Linn Damsgaard; Malene Norup Stolpe; Jesper Ninn Sandfeld Melcher; Jacob Wienecke; Glen Nielsen; Søren Smedegaard; Anne Husted Henriksen; Rasmus Ahmt Hansen; Charles H Hillman; Tuija H Tammelin; Geir K Resaland; et al. (BMC, 2024)
Abstract Background Previous research has suggested that school-based physical activity (PA) interventions may have a positive impact on academic performance. However, existing literature on school-based interventions encompasses various forms of PA, spanning from vigorous intensity PA outside the academic classes to light intensity PA and movement integrated into academic learning tasks, and results on academic performance are inconclusive. ACTIVE SCHOOL will implement two different PA interventions for one school year and assess the effects on the pupils' academic performance, with math performance as the primary outcome. Methods/design The ACTIVE SCHOOL project consists of two phases: 1) Development phase and 2) Randomized Controlled Trial (RCT). In phase one, two interventions were developed in collaboration with school staff. The two interventions were tested in an 8-weeks feasibility study. In phase two, a RCT-study with three arms will be conducted in 9-10-year-old children for one school year. The RCT-study will be carried out in two intervention rounds during the school years 2023/2024 and 2024/2025. Schools will be randomized to one of two interventions or control;1) Run, Jump & Fun intervention (4 × 30 min/week of moderate-to-vigorous physical activity; 2) Move & Learn intervention (4 × 30 min/week focusing on embodied learning in math and Danish lessons); or 3) a control condition, consisting of normal teaching practices. Outcome measures include academic performance, PA level, cognitive functions, cardiorespiratory fitness, anthropometry, well-being and school motivation (collected before, during and after the intervention period). A process evaluation will be conducted to assess implementation. Discussion The ACTIVE SCHOOL study will expand knowledge regarding the impact of PA on academic performance. The study will have the potential to significantly contribute to future research, as well as the scientific and educational debate on the best way to implement PA to support education and learning. Trial registration The study was registered on the 25th of October 2022 in ClinicalTrials.gov, NCT05602948.